Pengaruh General Reaction Score Terhadap Kadar Kortisol Darah Pada Wanita yang Terpapar Bising Pesawat Udara di Sekitar Bandara Adi Sumarmo Boyolali - Hartono (Jurnal Kedokteran Indonesia, 2009)
Background: Exposure to noise constitutes a health risk. There is sufficient scientific evidence thataircraft noise exposure can induce various disorders, such as hearing impairment, hypertension andischemic heart disease, annoyance, sleep disturbance, and decreased school performance. This studyaimed to examine the effect of the general reaction score on cortisol circulating levels of women withaircraft noise exposure in the area of Adi Sumarmo Airport of Boyolali.Methods: This was an analytical cross sectional study, conducted at the Dibal and Gagak Sipat Village,Ngemplak Sub district, Boyolali Central Java. The study was conducted from July 2008 to Juni 2009.The sample of 39 people was selected at random, divided into 3 groups: Group 1 was exposed 92.29dBnoise level (13 people), Group 2 was exposed 71.79 dB noise level (13 people), and Group 3 was exposedto 52.17 dB noise level (13 people). The data were analyzed by Pearson Correlation and Kruskal-Wallisfollowed by Pair-wise test.Results: Kruskal-Wallis test showed that there was a significant difference in cortisol circulating levelsstatistically in the groups (p = 0.018). Pearson correlation showed a positive association betweengeneral reaction score induced by aircraft noise exposure and circulating levels of cortisol (r = 0.47; p= 0.02).Conclusion: There is a significant effect of the general reaction score on cortisol circulating levels inwomen with aircraft noise exposure in the adjacent area.Keywords : aircraft noise, general reaction score, cortisol, Adi Sumarmo Airport